De David Belasco à Giacomo Puccini : La Fanciulla del West, premier opéra « américain » - Walter Zidaric (Revue LISA)
La Fanciulla del West is a “horse opera” resulting from the second collaboration between David Belasco and Giacomo Puccini. This work, specially composed for the American stage, which had its world premiere at New York’s Metropolitan Opera in December 1910, paved the way for American composers who increasingly focused on American History in their quest for a “national” opera. For the first time, Puccini resorted to genuine Indian music, a Zuni melody, which he re-elaborated for dramatic purposes and associated with the nostalgic mood of uprooted people, the miners who left their home country for America. The Other – the native American viewed from the vantage point of the white, as well as the foreigner – no longer represented a threat, as had been the case in the operatic repertoire before, but became part and parcel of a multicultural society, like the Italian immigrant to whom Puccini also paid tribute. The Zuni melody, which opens and closes the opera, contributes to giving a genuine twist to a score which is the first one to tackle the foundations of the American nation.